The Importance of Financial Incentives on Retirement Choices - Michele Belloni; Rob Alessie (Tinbergen Institute, 2008)
This study exploits a new dataset in order to quantify the effect of financial incentives on retirement choices. This dataset contains for the first time in Italy information on seniority. In accordance with the general finding in Gruber and Wise (2004), we find that financial incentives have an effect on retirement. The effect goes in the expected direction; when employees become eligible for pension benefits the change in financial incentives they experience is so high that their retirement probability increases in a sizable way. We also find that the procedure to impute seniority used in previous studies leads to a sizable measurement error. Due to this measurement error, the key parameters of the model are inconsistently estimated. Our sensitivity analysis suggests that the lack of appropriate information on seniority is an important reason for the unclear evidence so far obtained in retirement studies for Italy.
Keywords: J2; 330; retirement; social security wealth; seniority; unobserved heterogeneity; Gesetzliche Rentenversicherung; Ökonomischer Anreiz; Altersgrenze; Italien